2006
DOI: 10.1124/mol.105.021931
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen and Raloxifene Differ in Their Functional Interactions with Aspartate 351 of Estrogen Receptor α

Abstract: The bulky side chains of antiestrogens hinder folding of the ligand binding domain (LBD) of estrogen receptors (ERs) into a transcriptionally active conformation. The presence of a tertiary amine in the side chain of raloxifene, which interacts with a negatively charged residue in helix H3 of the ER LBD [Asp351 in human (h)ER␣], is important for antiestrogenicity in animal and cellular models. To better understand the molecular basis of the differential activity of tamoxifen and raloxifene, we have examined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 28 publications
3
23
0
1
Order By: Relevance
“…Previously, Mak et al (17) reported that the I362D mutation disrupted the recruitment of p160/SRC1 to the LBD; however, replacement to alanine (I362A) did not affect p160/SRC1 recruitment and transcription activity. There have been reports that altering the surface charge of H3 causes the antagonist reversal (22)(23)(24). The mutation of aspartic acid 351 on human ER␣ corresponding to mouse Asp-355 to tyrosine (hER␣-D351Y) enhances agonist activity of 4OHT and alters raloxifene from an antagonist to a partial agonist (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, Mak et al (17) reported that the I362D mutation disrupted the recruitment of p160/SRC1 to the LBD; however, replacement to alanine (I362A) did not affect p160/SRC1 recruitment and transcription activity. There have been reports that altering the surface charge of H3 causes the antagonist reversal (22)(23)(24). The mutation of aspartic acid 351 on human ER␣ corresponding to mouse Asp-355 to tyrosine (hER␣-D351Y) enhances agonist activity of 4OHT and alters raloxifene from an antagonist to a partial agonist (23).…”
Section: Discussionmentioning
confidence: 99%
“…Replacement of Asp-351 to alanine (hER␣-D351A) attenuated ligand (E2 and raloxifene)-mediated transactivation. In contrast, replacement to glutamic acid (hER␣-D351E) attenuated the E2-mediated transactivation but did not affect raloxifene-mediated transcription (24). Importantly, the residues of mouse I362 corresponding to human Ile-358 and human Asp-351 are localized on the same surface of H3 forming a highly conserved region between mouse and human ER␣.…”
Section: Discussionmentioning
confidence: 99%
“…Mutation D351G abrogated induction of expression of the estrogen target gene TGFA by tamoxifen in transfected MDA-MB-231 cells (MacGregor Schafer et al . 2000), and mutation D351A abolished partial activity of ERα on a reporter gene in the presence of tamoxifen in HepG2 cells (Dayan et al . 2006), consistent with a role of Asp351 in mediating the partial agonist activity of SERMs in the absence of optimal interaction with their side chain tertiary amines.…”
Section: Molecular Determinants Of Antiestrogenicitymentioning
confidence: 99%
“…In support of this mechanism, modifications to the pendant side chain of tamoxifen that alter the nature of the azacycle, while preserving the tertiary amine functionality, show dramatic differences in the level of transcriptional activation in cell-based assays (Dayan et al 2006). Abolition of the negative charge at Asp 351, by mutation of this residue to Ala or Val, greatly reduced the propensity for transcriptional activation in tamoxifen derivatives, regardless of the chemical structure of the terminal azacycle (Dayan et al 2006). Similarly, Webb et al (2003) have reported differential effects of tamoxifen and raloxifene on recruitment of corepressor proteins.…”
Section: Discussionmentioning
confidence: 96%
“…Such a repositioning of AF-2 has been demonstrated to be critical for corepressor recruitment in the case of PPARa bound to a potent antagonist (Xu et al 2002), and Nettles and Greene (2005) have suggested a similar mechanism at work in ERa. In support of this mechanism, modifications to the pendant side chain of tamoxifen that alter the nature of the azacycle, while preserving the tertiary amine functionality, show dramatic differences in the level of transcriptional activation in cell-based assays (Dayan et al 2006). Abolition of the negative charge at Asp 351, by mutation of this residue to Ala or Val, greatly reduced the propensity for transcriptional activation in tamoxifen derivatives, regardless of the chemical structure of the terminal azacycle (Dayan et al 2006).…”
Section: Discussionmentioning
confidence: 98%